Post Storage Physiology and Vase life of low Temperature Stored Tuberose Cut Spikes as Influenced by α-Lipoic Acid and Polyfilm Packaging - Sahare, Homraj A.; Singh, Alka; Chavan, Sachin; Chawla, S. L.; Bhanderi, D. R. (Asian Journal of Biological and Life Sciences, 2015)
Effect of antioxidant, α-lipoic acid along with sugars as pre-storage pulsing treatment and seal packaging with polyfilms viz., HDPE(40µ), LDPE (40µ) PP (40µ) and PP(30µ) at low temperature (2°C) storage for 15 days on post storage physiology and life of tuberose cut spikes were investigated. Pre-storage pulsing of tuberose cut spikes with solution containing 50mg l-1 α-lipoic acid + 15% sucrose for six hours and seal packaging with HDPE 40 µ poly film significantly influenced spike fresh weight, petal total soluble sugar level, PAI (%) in floret tissue in low temperature stored cut spikes. Untreated low temperature stored tuberose cut spikes displayed drastic chilling injury and reduced vase life to 0-3 days after low temperature storage. These results suggest that prestorage pulse treatment of tuberose cut spikes with α-lipoic acid and packaging with HDPE during low temperature storage at 2°C temperature retains higher spike fresh weight, petal sugar levels, and stabilizes cell membrane integrity in petal tissue leading to a delay in petal senescence with 7 days of vase life even after 15 days of cold storage.
Keywords: FW; PAI etc.; TSS; Tuberose; α-lipoic acid